A brain-enriched polypyrimidine tract-binding protein antagonizes the ability of Nova to regulate neuron-specific alternative splicing - Polydorides, Alexandros D. (National Academy of Sciences, 2000)
The Nova paraneoplastic antigens are neuron-specific RNA binding proteins that participate in the control of alternative splicing. We have used the yeast two-hybrid system to isolate Nova interacting proteins and identify an RNA binding protein that is closely related to the polypyrimidine tract-binding protein (PTB). The expression of this protein, brPTB, is enriched in the brain, where it is expressed in glia and neurons. brPTB interacts with Nova proteins in cell lines and colocalizes with Nova within neuronal nuclei. We previously found that Nova binds to a pyrimidine-rich RNA element present upstream of an alternatively spliced exon, E3A, in glycine receptor α2 (GlyRα2) pre-mRNA, and this binding is implicated in Nova-dependent regulation of splicing. Cotransfection assays with a GlyRα2 minigene demonstrate that brPTB antagonizes the action of Nova to increase utilization of GlyRα2 E3A. brPTB binds to a 90-nt GlyRα2 RNA adjacent to the Nova binding site, but with an affinity that is more than 10-fold lower than Nova. When a putative binding site for brPTB on the GlyRα2 RNA is mutated, binding is abolished and the inhibitory effect on Nova-dependent exon selection disappears. These results suggest that brPTB is a tissue-restricted RNA binding protein that interacts with and inhibits the ability of Nova to activate exon selection in neurons.